Hubungan Shift Kerja Dengan Tingkat Stres Kerja Perawat Di Instalasi Gawat Darurat (IGD) - Dangkua, Wahyu Pratama S.; Dulahu, Wirda Y; Hunawa, Rachmawaty D.; Hiola, Dewi Suryaningsi (An Idea Health Journal, 2024)
Work shift is determined as one of the triggering factors of stress in nurses. The existing demand for maximum patient service forces the nurses work in shifts. This study then aimed to determine the correlation of work shifts to the level of work stress of nurses in the Emergency Room (ER) at the Regional Public Hospital Prof. Dr. H. Aloei Saboe Gorontalo. This study was conducted using a quantitative method and a cross-sectional design. The study population was all nurses in the Emergency Room (ER) of RSUD Prof. Dr. H. Aloei Saboe, Gorontalo, and they were collected using the total sampling technique. Then, the data were analyzed using the Kolmogorov-Smirnov test. The finding showed a correlation between work shifts and the level of work stress of nurses in the Emergency Room (ER) at RSUD Prof. Dr. H. Aloei Saboe, Gorontalo (p=0,033) this study is expected to provide the knowledge for all nurses to continue prioritizing professionalism at work, especially in providing services to patients, and at the same time exploring their stress management strategies while working